Digestive enzymes of Greater wax moth (Galleria mellonella) (Lepidoptera: Pyrilidae) through some strains of endophytic fungi infection (Journal of Pharmaceutical Negative Results, 2022)
This study was carried out to investigate the effect of endophytic fungi on physiological responses of Galleria mellonella (G. mellonella). The analyses of some parameters have been recorded as influenced by the filtrate of A. nidulans, A. flavus and A. niger. For, A. niger, the total larval toxicity index reached 99.4 % for the least used median lethal concentration of LC50 (11.96).The fungal filtrate of A. nidulans, A. flavus and A. niger had satisfactory levels of mortality compared with those of fungal spore suspension that exhibited less levels of mortality. The results were recorded at different incubation intervals (1, 2, 3, 5, 7, 9 and 11 days) and the obtained data were recorded in table. The results revealed 8 % of fungal filtrate showed a great mortality (70%) than other concentrations. More than 8 % of fungal filtrate decreased larval mortality. It can be concluded that 4 % and 5 % of fungal filtrate of the three fungal strains produced significant increase in larval mortality, as compared with other concentrations.A. flavus AUMC 13942 was superior for either trehalase and amylase activity of the experimental fungal strains. A. flavus AUMC 13942 was found to be the most effective fungal strains and produced significant differences (P ≤ 0.05) in trehalase and amylase activity. The highest trehalase activity values obtained by A. flavus AUMC 13942 strain was 14.22 mg glucose\ g. b. wt\ min after 7 days and the highest invertase activity values obtained by A. nidulans AUMC 13941 strain after 9 days were and 13.42 mg glucose\ g. b. wt\ min by, respectively compared to control.